Core-shell microcapsules: biofabrication and potential applications in tissue engineering and regenerative medicine - Ladeira, Bruno M. (2023)
The fabrication of scaffolds that accurately recreate the architecture of living tissues is a major challenge in the field of tissue engineering and regenerative medicine. Core-shell microcapsules hold great potential in this regard, as they can recreate the hierarchical structure of biological systems. The independent modulation of the composition of both core and shell layers allows the design of compartmentalized platforms tailored to the recreation of specific cell niches. Emergent technologies such as superhydrophobic surfaces, microfluidics, electrospray, and layer-by-layer assembly have been successful in producing core-shell microcapsules for the encapsulation of cells and bioactive factors. This review provides an overview of available materials and techniques used in the generation of core-shell microcapsules, while also highlighting some of their potential applications in the design of innovative and effective tissue engineering and regenerative medicine strategies.